Design, synthesis and characterization of MOF-199 and ZIF-8: Applications in the adsorption of phenols derivatives in aqueous solution - Giraldo, Liliana; Bastidas-Barranco, Marlon; Húmpola, Pablo; Moreno-Piraján, Juan Carlos (European Journal of Chemistry, 2017)
In this work, the adsorption characteristics of metal-organic frameworks (MOFs: MOF-199 and ZIF-8) with two different types of structure were analyzed. MOF-199 consists of copper-based metal clusters while the ZIF-8 consists of organic molecules interlaced with zinc atoms and these have octahedral morphology and typical rhombic dodecahedron shape, respectively. The results of phenol (Ph) and p-nitro phenol (PNP) adsorption capacity from aqueous solution show that MOF-199 has a higher adsorption capacity: Ph 79.55% and PNP 89.3%, while for ZIF-8 the adsorption capacity was Ph 65.5% and PNP 77.0%. Adsorption of phenols was fit to Langmuir, Sips and Redlich-Peterson models and kinetics by pseudo-second order. Gibbs free energy (ΔG°) shows that adsorption processes studied are spontaneous.